Promoter's Effect on the Properties of Steam Reforming Catalyst (Chemical Engineering Research Bulletin, 2008)
During this study, a number of catalysts were prepared following two methods and varying the catalyst components. Manganese and magnesium nitrates were used as promoters to nickel-aluminium catalytic system. Both the magnesium and manganese increased the reaction rate but significant promoting effect of manganese was observed under studied conditions. Among the developed catalyst preparation methods, Method-l was found to be the best for Ni/Al/Mn catalyst. This investigation has led to the development of a Ni/Al/Mn catalytic system which is found to be comparable to an industrial secondary reforming catalyst produced by CCIFE in respect of initial intrinsic rate.Chemical Engineering Research Bulletin 10 (2006) 64